Unravelling the drivers behind COVID-19 vaccination hesitancy and refusal among teachers: A nationwide study - Estrela, Marta (2022)
This study aims to assess the determinants of the coronavirus disease 2019 (COVID-19) vaccination hesitancy and refusal (VHR) among teachers, from pre-school to higher education, through an online survey. A logistic regression analysis was used to determine the adjusted odds ratio (OR) of the independent variables (perceptions, knowledge, and attitudes) per 1-point increase in the Likert scale, and VHR. Concerns about the vaccines' efficacy and safety increase the risk of VHR (OR = 6.97, 95 %CI: 4.82-10.09 and OR = 8.71, 95 %CI: 5.52-13.73, respectively). Higher risk perceptions of getting infected (1/OR = 3.94, 95 %CI: 2.93-5.29), trust in the effectiveness of vaccines in reducing this risk or protecting against suffering complications (OR = 3.52, 95 %CI: 2.72-4.55 and OR = 10.94, 95 %CI: 7.16-16.68, respectively), and higher trust levels on the information transmitted regarding COVID-19 vaccination, are associated to lower VHR. As VHR appears to be highly influenced by perceptions, knowledge, and attitudes, it is crucial to promote and design interventions targeted to transforming these determinants.